Clark’s Technique of Vestibuloplasty - A Case Report - Shrestha, Benju; Lamichhane, Krishna Prasad; Pradhan, Shaili; Gorkhali, Ranjita Shrestha; Koirala, Pramod Kumar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Shallow vestibule can create a barrier in oral hygiene maintenance and can cause gingival recession due to the muscular traction. Inadequate vestibular depth in combination with inadequate attached gingiva is said to cause more food accumulation during mastication. Hence, shallow vestibule impeding with oral hygiene maintenance requires correction. Vestibuloplasty involves surgical procedure for repositioning of mucosa and muscle attachment thereby increasing the vestibular depth. There are various techniques of vestibuloplasty. This case report highlights upon the Clark’s technique of vestibuloplasty for correction of shallow vestibule.